Hak Asasi Manusia (HAM) Sebagai Bentuk Kebijakan Politik Dalam Pelaksanaan Perlindungan - Shinta Azzahra Sudrajat (Definisi: Jurnal Agama dan Sosial Humaniora, 2022)
Human rights are a problem, which cannot be ignored for any reason, including in Indonesia, actually it is exigent to have a human rights law enforcement. Human rights enforcement law is a policy to protect human rights. In human rights principles, the state is a human rights holder and every individual under its auspices is a human rights holder. A country has an obligation to respect, fulfill and protect its people. In addition to these obligations, the state also has a responsibility in solving problems regarding human rights violations that occur to try and enforce the rights for human. Society is a social creature that needs a handle in its life, norms are born as written and unwritten laws. Aims to provide justice in its place. Human rights describes the state's position on human rights issues.